English language learner beliefs and speaking anxiety of diploma level students in UiTM Kota Samarahan / Dayang Zarinah Awang Bohari - Awang Bohari, Dayang Zarinah (2011)
Speaking anxiety is one of the most pressing problems that both learners and instructors of a language are likely to experience or encounter. This is especially so when the target language is not the speaker’s native or first language. In fact, it would be a foreign language or a second language. While in some cases the anxiety may produce positive results, more often than not the opposite happens. Related to anxiety is the learner’s set of beliefs which can affect the teaching as well as the learning process. The objectives of the present study were to identify learners’ speaking anxiety levels and also their language learning beliefs. In addition, the research also aimed to investigate if there was a relationship between speaking anxiety and beliefs. The study employed a quantitative method of research for data collection and analysis. Findings showed varying levels of speaking anxiety, a range of positive as well as negative beliefs associated with language learning and different relationships for different belief items. The findings from this study could be used to further enhance learning and teaching in the second language classroom with respect to motivation, strategies and resource materials for the learners of the target language. It is hoped that the implications will benefit all language learners and the weaker ones in particular.